di Analisis Framing Pemberitaan Kasus Korupsi Syahrul Yasin Limpo di Kompas.com - Ahmad Fauzan Akbar (Program Studi Penerbitan, Politeknik Negeri Jakarta, 2025)
Corrupt practices in Indonesia are a major problem that causes financial losses and undermines public trust in government and justice. This phenomenon has become a widespread habit from before independence to the Reform era, and involves various levels of government. The mass media plays an important role in publicizing corruption cases, shaping public opinion, and influencing the political agenda. This study aims to analyze the framing of the news coverage of the Syahrul Yasin Limpo corruption case by Kompas.com from February 29 to May 10, 2024. The framing analysis method is used to observe how the media shapes reality and presents news, as well as identify power dynamics and relationships between the parties involved. The results of the study show that Kompas.com focus on certain aspects that affect the public's view of the case. This study provides an understanding of the influence of media framing on public perception of corruption cases in Indonesia.